Policy Space in a Financially Integrated World: The Brazilian Case in the 2000s - Feijo, Carmem; Tostes Lamonica, Marcos (Panoeconomicus, 2018)
This paper makes the argument that policy space in Brazil has been narrowing since the trade and capital opening made in the 1990s. This is so because the opening of the Brazilian economy has implied that real and nominal interest rates have been kept high and the real exchange rate has shown a trend towards appreciation. The behavior of the main macroeconomic prices of the Brazilian economy brought, as a minimum, two negative results to economic growth. On one hand, the annual average growth rate was reduced because structural change had been moving towards less technologically productive sectors, which deepened deindustrialization. On the other hand, short-term economic growth had become more volatile, given that the evolution of the investment position of the country increased its potential degree of external fragility.Key words: Policy space, Brazilian economy, Balance of payment dominance.JEL: O11, O14.Politički prostor u finansijski integrisanom svetu: slučaj Brazila 2000-ihU radu je argumentovano da se politički prostor u Brazilu sužava od uvođenja trgovinske i kapitalne otvorenosti tokom 1990-ih. To je tako zato što je otvaranje brazilske ekonomije impliciralo da su realne i nominalne kamatne stope držane na visokom nivou i da je realni devizni kurs pokazao trend ka apresijaciji. Ponašanje osnovnih makroekonomskih cena brazilske privrede dovelo je do, najmanje, dva negativna ishoda po ekonomski rast. S jedne strane, godišnja prosečna stopa rasta je smanjena zato što su se strukturne promene kretale ka manje tehnološki produktivnim sektorima, što je produbilo deindustriјalizaciju. S druge strane, kratkoročni ekonomski rast je postao nestabilniji, s obzirom na to da je razvoj investicione pozicije zemlje povećao njen potencijalni stepen spoljne osetljivosti.Ključne reči: Politički prostor, brazilska ekonomija, dominacija platnog bilansa.